Genome‐wide survey of copy number variants finds MAPT duplications in progressive supranuclear palsy. Issue 7 (6th May 2019) - Chen, Zhongbo; Chen, Jason A.; Shatunov, Aleksey; Jones, Ashley R.; Kravitz, Stephanie N.; Huang, Alden Y.; Lawrence, Lauren; Lowe, Jennifer K.; Lewis, Cathryn M.; Payan, Christine A. M.; Lieb, Wolfgang; Franke, Andre; et al.
Abstract: Background: Progressive supranuclear palsy is a neurodegenerative tauopathy manifesting clinically as a progressive akinetic‐rigid syndrome. In this study, we sought to identify genetic variants influencing PSP susceptibility through a genome‐wide association analysis of a cohort of well‐characterized patients who had participated in the Neuroprotection and Natural History in Parkinson Plus Syndromes and Blood Brain Barrier in Parkinson Plus Syndromes studies. Methods: We genotyped single‐nucleotide polymorphisms in 283 PSP cases from the United Kingdom, Germany, and France and compared these with genotypes from 4472 controls. Copy number variants were identified from genotyping data. Results: We observed associations on chromosome 17 within or close to the MAPT gene and explored the genetic architecture at this locus. We confirmed the previously reported association of rs1768208 in the MOBP gene ( P = 3.29 × 10 ‐13 ) and rs1411478 in STX6 ( P = 3.45 × 10 ‐10 ). The population‐attributable risk from the MAPT, MOBP, and STX6 single‐nucleotide polymorphisms was found to be 0.37, 0.26, and 0.08, respectively. In addition, we found 2 instances of copy number variants spanning the MAPT gene in patients with PSP. These copy number variants include tau but few other genes within the chromosome 17 haplotype region, providing additional support for the direct pathogenicity of MAPT in PSP. Conclusions: Clinicians should also be aware of MAPT duplication as a possible genetic cause of PSP, especially in patients presenting with young age at onset. © 2019 International Parkinson and Movement Disorder Society